Surgical recurrence of solitary fibrous tumor of the pleura treated with microwave (MW) thermoablation: A case report - Francesco Fiore; Vincenzo Stoia; Francesco Somma (Thoracic Cancer, 2020)
Abstract Solitary fibrous tumor (SFT) of the pleura is a rare neoplasm which is challenging for clinicians to treat and radiologists to diagnose. Herein, we report a case of recurrence of SFT of the pleura in a 77‐year‐old patient which was diagnosed and surgically treated on the first occasion in 2005. The patient had a recurrence in 2016 which was treated and then six months later, he again experienced chest pain and a further local recurrence was found. Taking into consideration the age and comorbidities of the patient, CT‐guided percutaneous microwave‐thermal ablation was preferrable to surgery and a safe and highly effective local ablative technique with few side‐effects.